Generasi milenial dan pengembangan museum Geopark Batur pada era adaptasi kebiasaan baru pandemi Covid-19 - Ni Putu Somawati; Gede Ginaya; Ni Putu Wiwiek Ary Susyarini; Ni Made Sudarmini (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Behind the COVID-19 pandemic that has hit the whole world, there are blessings in disguises. One of them is millennial students can utilize the museum as a means of developing values of their characters. The purpose of this study is to examine the contribution of millennials to the development of Batur Geopark Museum. By applying a qualitative research method, the primary data were collected through observations and interviews. Secondary data was obtained from relevant authorities, news, and literature reviews. The results of the study explain the mutual benefits between students and the Batur Geopark Museum. For millennial students, they benefit in the form of visual references and experiences of past historical events. On the other hand, the Batur Geopark Museum get leverage from the millenials’ visits through on the job training (OJT) programs and student industrial visits. This will be followed by information exchange, social media activities and enhanced electronic word-of-mouth (EWOM).